2012
DOI: 10.1038/ijosup.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Development, brain plasticity and reward: early high-fat diet exposure confers vulnerability to obesity—view from the chair

Abstract: The significant increase in childhood obesity has become a particular concern, and it is recognized that the programming of obesity can arise from events occurring in the peri-conception period, prenatally and/or during the early postnatal period. In particular, high intake of dietary fat by the mother has long-term effects that are worse than once thought. This symposium was designed to outline some of the important consequences of maternal high-fat feeding during gestation and lactation, as well as exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…A consensus has emerged that early life exposure to a maternal obesogenic environment increases the risk of developing obesity and metabolic disorders in adulthood. However, there is less agreement on the mechanisms through which such risk may be conferred ( 4 ). Collectively, data to date reveal that leptin, in particular, and ghrelin play key roles in facilitating the normal development of hypothalamic neural circuits and suggest that normal expression of these factors during the fetal/neonatal period is key for lifelong metabolic regulation ( 55 , 86 , 102 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A consensus has emerged that early life exposure to a maternal obesogenic environment increases the risk of developing obesity and metabolic disorders in adulthood. However, there is less agreement on the mechanisms through which such risk may be conferred ( 4 ). Collectively, data to date reveal that leptin, in particular, and ghrelin play key roles in facilitating the normal development of hypothalamic neural circuits and suggest that normal expression of these factors during the fetal/neonatal period is key for lifelong metabolic regulation ( 55 , 86 , 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to homeostatic systems responsive to nutrient sensing and regulation of energy balance, maternal obesity can also perturb the hedonic system which includes stimuli related to reward and cognitive factors ( 4 ). In the context of early life developmental programming, exposure to HF/high-sugar diets has been shown to result in altered development of central reward systems, leading to increases in fat intake and altered responsiveness of the hedonic reward system to over consumption of energy-dense food in offspring in later life ( 32 ).…”
Section: Epigenetics and The Reward Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of both anorexogenic and orexogenic genes may just explain the absence of changes on food intake and body weight observed in previous studies (Cho et al 2013a;Cho et al 2014). Moreover, gene changes were not sustained across weaning and postweaning, which may only indicate brain plasticity during different windows of development (Hanson et al 2011;Walker 2012).…”
Section: Discussionmentioning
confidence: 73%
“…In animal models, it has also been shown that a change in synaptic activation (synaptic plasticity) is induced in the reward system [16] followed by an inadequate response to the consumption of highly energetic food in concomitance with the pregnancy period [10,25]. This is due to the epigenetic alteration of the expression of dopamine and opioid-related genes present in the mesocorticolimbic circuits [26].…”
Section: How Can Negative Environmental Conditions Influence the Devementioning
confidence: 99%